Geoturism: Some Examples from Turkey - Kaygili, Sibel; Sinanoglu, Derya; Aksoy, Ercan; Sasmaz, Ahmet (Dnipropetrovsk Natl Univ Oles Gonchar, 2018)
Geotourism is one of the most important tourism sectors that has rapidly developed and become widespread in recent years. Geotourism is defined as tourism that sustains or enhances the distinctive geographical character of a place-its environment, heritage, aesthetics, culture, and the well-being of its residents. The purpose of geotourism is to recognize and protect these natural structures of public, as well as contributing to local and regional development through the emerging species. Geotourism incomes have begun to increase in the total tourism incomes of the countries. There are many places in Turkey that can be considered as possible areas of geotourism. In this scope; Cappadocia fairy chimneys, Manisa Kula volcanic area, Denizli Pamukkale travertines and Bitlis Nemrut Caldera were studied.
Keywords: Geotourism; Turkey; Cappadocia; Kula Geopark; Pamukkale; Nemrut Caldera